Direct Assistance Cash in Central Sulawesi - Perwira, M. Adnan Latief; Hakim, Lukman; Daerobi, Akhmad (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2025)
This study aims to analyse the influence of factors such as letters of incapacity, elementary schools, junior high schools, and high schools, as well as the number of electricity customers, health facilities, income sources, and COVID-19, on direct cash assistance. The OLS method is used to study the letter of incapacity, elementary schools, junior high schools, high schools, the number of electricity customers, health facilities, income sources, and COVID-19 on direct assistance cash at the village-level unit of 2020 villages. The research approach uses a descriptive quantitative approach. The data collection technique used by the researcher is derived from village potential data released by the Central Statistics Agency in 2021. The study sample consisted of 2020 villages. This study uses a multiple linear regression equation model. The research findings indicate that high schools, electricity customers, and COVID-19 do not have a direct impact on cash assistance. Letters of incapacity, income sources, elementary schools, and junior high schools have a positive and significant effect. In contrast, the number of health facilities has a negative and significant impact on direct cash assistance. The results of this study are expected to form the basis for policy recommendations to support government programs to increase economic growth and poverty alleviation through direct cash assistance